Tobacco use trends among youth in Saudi Arabia: 2007–2022 - Monshi, Sarah S.; Desouky, Eman D. El; Aldukhail, Shaikha K.; Al-Zalabani, Abdulmohsen H.; Alqahtani, Mohammed M.; Dalatony, Mervat M. El; Shubayr, Mosa A.; Elkhobby, Ahmed A.; Aldossary, Mohammed S. (Frontiers in Public Health, 2025)
IntroductionTobacco use is a major global public health challenge, causing millions of deaths annually. In Saudi Arabia, increasing adult smoking rates highlight the need for improved tobacco control measures.AimThis study examined trends in tobacco use among youth in Saudi Arabia from 2007 to 2022, evaluating shifts in the determinants of tobacco use and the effectiveness of control measures over time.MethodsWe analyzed three waves of the Global Youth Tobacco Survey (GYTS) conducted in Saudi Arabia (2007, n = 2,574; 2010, n = 1,797; 2022, n = 5,610). The GYTS uses a two-stage cluster sampling design to select students aged 13–15 from intermediate schools, with a focus on tobacco use trends and related behaviors.ResultsThis study revealed a substantial decline in current tobacco product usage, dropping significantly from 15.9% in 2007 to 9.4% in 2022 (B = −0.44, p = 0.030), and a decrease in exposure to second-hand smoke from 27.9% in 2007 to 18.1% in 2022. However, the proportion of individuals aged 7 years or younger who initiated cigarette smoking rose from 9.1% in 2007 to 17.1% in 2022. There was a 6.4% increase among female youth who thought that smoking made people feel comfortable across this time period (B = 0.55, p = 0.033), and this population demonstrated a significant decrease in the intention to quit smoking from 65.7 to 52.2% (B = −0.895, p = 0.010).ConclusionAlthough overall tobacco use decreased, alarming trends, emerged, such as earlier smoking initiation and declining intentions to quit among females. Future interventions should focus on preventing early tobacco use initiation by addressing misconceptions, promoting cessation, and enforcing restrictions on youth access to tobacco products.